International spillovers in inflation expectations - Matteo Ciccarelli; Juan Angel García (European Central Bank (ECB), 2015)
This paper investigates the factors behind developments in inflation expectations in euro area, the U.S. and the U.K. over the sample 2005-2015. Our analysis unveils the presence of a quantitatively important spillover from euro area long-term inflation expectations onto international ones, in particular the U.S., since August 2014. This finding has some important implications. From a policy perspective, it contributes to explain the somewhat puzzling declines in financial indicators of inflation expectations since the autumn 2014 (Yellen, 2015). From a research perspective, our findings suggest that the relatively weak performance of term-structure models (and other econometric models) to explain developments in long-term inflation expectations in major economic areas over 2014-15 may be due to the omission of international factors. These two dimensions may well carry a significant weight on the on-going and future debate on monetary policy normalisation in major central banks.
Keywords: C11; C52; E31; 330; deflation; global inflation; inflation expectations; international spillovers